Accelerated Resolution Therapy: Randomized Controlled Trial of a Complicated Grief Intervention. (October 2020) - Buck, Harleah G.; Cairns, Paula; Emechebe, Nnadozie; Hernandez, Diego F.; Mason, Tina M.; Bell, Jesse; Kip, Kevin E.; Barrison, Philip; Tofthagen, Cindy
Background and Objectives: Complicated grief (CG) is severe, prolonged (>12 months) grieving. Complicated grief disproportionately affects older adults and is associated with negative physical/psychological effects. Although treatment options exist, those which do are time-intensive. We report on a randomized clinical trial (RCT) which examined whether accelerated resolution therapy (ART), a novel mind-body therapy, is effective in treating CG, post-traumatic stress disorder (PTSD), and depression among hospice informal caregivers. Research Design and Methods: Prospective 2 group, wait-listed RCT. All participants were scheduled to receive 4 ART sessions. Inclusion: ≥60 years, inventory of CG >25, and PTSD checklist for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition >33 or Psychiatric Diagnostic Screen Questionnaire PTSD subscale >5. Exclusion: Major psychiatric disorder, other current psychotherapy treatment. Depression was measured by the Center for Epidemiologic Studies Depression. Results: Mean (standard deviation [SD]) age of 54 participants was 68.7 (7.2) years, 85% female, and 93% white. Participants assigned to ART reported significantly greater mean (SD) CG reduction (−22.8 [10.3]) versus Wait-list participants (−4.3 [6.0]). Within-participant effect sizes (ESs) for change from baseline to 8-week post-treatment were CG (ES = 1.96 (95% confidence interval [CI]: 1.45-2.47; P < .0001), PTSD (ES = 2.40 [95% CI: 1.79-3.00]; P < .0001), depression (ES = 1.63 [95% CI: 1.18-2.08; P < .0001). Treatment effects did not substantially differ by baseline symptom levels. Discussion and Implications: Results suggests that ART presents an effective and less time-intensive intervention for CG in older adults. However, it should undergo further effectiveness testing in a larger, more diverse clinical trial with a focus on determining physiological or behavioral mechanisms of action.